Evento de movimento transitivo: uso, cognição e rede construcional - César, Alan Marinho (2020)
In this thesis, I examine the semantic and syntactic coding of transitive motion events with the goal of dealing with the relationship between the type of event expressed by the transitive motion construction (TMC) and the cognitive schemes triggered by it. I conceptualize the transitive motion verb (TMV) as one that is complemented by two or three arguments that imply the movement of at least one entity from one place to another. Based on the observation of the contexts of use of constructs with this verb, I propose a hierarchical construction network that accommodates the different patterns that can instantiate a transitive motion construction (TMC), considering aspects of the TMV's argumentative configuration, and the cognitive schemes underlying these patterns. The theoretical basis of this thesis combines assumptions stemming from Functional Linguistics Focused on Use - Linguística Funcional Centrada no Uso (LFCU - acronym in Portuguese), Cognitive Linguistics (CL) and Construction Grammar (CxG). The analytical categories adopted are mainly related to transitivity, semantic roles, prototypicity, frame semantics, image schemes and conceptual metaphors. The research carried out is characterized as deductive using a mixed methodological approach (qualitative and quantitative). The data supporting the analysis were collected from different sources: O Corpus Discurso & Gramática - Corpus Discourse & Grammar, the JFRN’s Sentencing Bank, the Database of the “Program for Studies on the Use of Language at UFRJ” (Project PEUL - acronym in Portuguese), and texts available online on websites of widely circulated magazines. The search results revealed the existence of a construction scheme organized syntactically as subject noun phrase NPSUBJECT + VMOTION + object noun phrase (NP Od) + prepositional phrase (PP) which sanctions three subschemas and seven micro-constructions, which, in turn, reveal notions of caused-motion, traveled-motion and associated-motion.